A Project feasibility study of "Print House, Inc." - Ines, Romeo, Jr.; Palana, Josemarianito; Ericta, Jean.; Santos, Eric.; Domingo, Felizardo (Diliman, Quezon City College of Engineering, 1989)
The printed word is one of the most effective catalysts for change and development. It is not only a vital medium for information dissemination but it also preserves knowledge intrinsic in educating people. Print is vital in business - sells products and service, makes possible identification of money, postage, trademarks and packaging of products. It is essential in public administration and an effective channel of entertainment. These and a lot more reasons bring to the fore the printing, publishing, and allied industries. The demand for printing is basically composed of the local demand and the export demand. The local demand is primarily satisfied through local production and importation. Through the years, the number of publications has immensely multiplied and there is a limitless dimension off topics printed most of which are printed either in English of Filipino while others are in Chinese or local dialects. However, despite the number of local publications being circulated in the country, most of the publications which are widely circulated are foreign materials. A significant portion of demand has been supplied through imports which substantially exceeded exports by 67.44 million dollars from 1987 to 1989. But while we rely on imports to meet part of our domestic needs for printed materials, the Philippines managed to export some of its locally produced printed matters. And if local printers can displace even a half of our yearly imports of printed matter, this would mean additional business of about 280.5 million dollars yearly. But to realize this goal, some of the existing equipments and technological methods will have to be modernized. Also, a very good marketing strategy is required. The more crucial points in assuring a market are efficiency in operations, quality in the finished product and competitiveness in pricing. Customer satisfaction, of course, is the focal point as the printing business is highly volatile with respect to customer loyalty. The trend, at present, is in improving final outputs by a combination of sound marketing strategy formulation and technical enhancement. This is precisely why the number of printers is decreasing while the corresponding size is increasing. This only shows that customers flock to those printers who offer the better deal, leaving the rest no choice but to either close shop or sell to bigger establishments. The proposed printing press can print anything on paper. The only limitation will be the sheet size of the paper. Two kinds of printing techniques will be utilized, depending on the type of printing job: offset printing and letterpress printing. In these processes will be incorporated the latest printing techniques, including desktop publishing. The use of modern equipment and machinery will ensure that the printing firm remains efficient and competitive. All in all, the company will employ a total of 25 employees, skilled as well as unskilled. The raw materials basically consist of paper, ink and chemicals. All of these are easily available in the locality. Likewise, the utilities needed, such as electricity, water and telephones are readily available. The plant generates recyclable and non-toxic wastes that may be conveniently disposed of. The plant will be located in the Scout Area of Quezon City. Land will be bought and a new one-storey building will be erected on the land site. Total project cost for the proposed printing firm is about 6 million dollars. Based on the total project cost and the revenues generated for five years, a favorable internal rate of return of 27.8% was calculated. Figures for revenues and costs were calculated from projections of sales based on sample printing jobs. Other costs were taken from surveys done on printing firms of similar sizes. Financing will be availed primarily through equity and through loans from commercial banks. It is expected that within five years, the company will be able to fully amortize the said loans. The proposed printing press will be beneficial to the community and the country at large, in the following ways: 1. It will create employment to a number of people. 2. It will help fill the gap of printing needs of the country. 3. It could generate foreign exchange income and savings. 4. It will assist the literacy and educational development of the country. 5. It will support the government in the form of payment of taxes. And 6. It will help the economy through investment spending. Based on the favorable analyses of the marketing, technical, financial and social profitability aspects of the printing press, we recommend the project to be undertaken. Focus on the following pints will be very helpful in making the printing firm a successful endeavor: 1. A dynamic marketing strategy. 2. An efficient production scheduling. 3. Proper technical knowledge. 4. Careful price monitoring. And 5. Well defined financial planning.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Print House, Inc; Printing industry; Participatory monitoring and evaluation (Project management)